Antioxidants in bioremediation of chromium (VI) by conventional and nanotechnological approaches: a review. Issue 2 (7th February 2021) - Babangida, Sanusi Katsayal; Muhammad, Aliyu; Garba, Auwalu; Sallau, Abdullahi Balarabe
Abstract: Hexavalent chromium has been widely distributed in the environment by natural and anthropogenic sources characterized by higher toxicological and solubility properties than the trivalent form. Remediation-by-reduction of chromium (VI) to chromium (III) through the use of chemicals has offered an environmental and cost-effective approach for chromate detoxification. One of the major disadvantages of chemical reduction is that the addition of reductant constitutes a secondary source of contamination; for instance, sodium dithionite at low pH can decompose to sulfur dioxide which can irritate the skin and respiratory tract. In this review, the application of safer reductants of conventional and nanotechnological approaches is addressed. The use of antioxidant biomaterials for chromium (VI) remediation may offer benign alternatives to the use of chemical reductants.